Indonesia's Constitutional Transformation: A Critical Analysis of the Amendments to the 1945 Constitution from a Modern Constitutional Perspective - Yormi, Yormi (Yayasan Zia Salsabila, 2024)
This research aims to analyze Indonesia's constitutional transformation after the amendments to the 1945 Constitution, with a focus on significant changes in the constitutional system and their impact on democracy. Although the amendment aims to strengthen the system of checks and balances and encourage more democratic governance, its practice shows a mismatch between constitutional theory and implementation on the ground. This research uses a qualitative approach with document analysis and interviews, as well as analyzing data using software to identify patterns in legal documents and the views of constitutional experts. The research results show that although the amendment strengthens the position of the legislature, the concentration of power in the executive and inequality in the distribution of power between the center and the regions remain the main challenges. The implication of these findings is the need for further efforts to increase the effectiveness of the system of checks and balances and decentralization of power. This research's recommendations include strengthening the role of the legislature and improving the decentralization system to create a fairer and more responsive government.